The Effect of Service Quality and Image of the International Class and ESchool Program of the Faculty of Economics and Business, Pasundan University on Student Satisfaction - Rifa Fauziah; Undang Juju; Wasito Wasito; Popo Suryana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of service quality and program image on student satisfaction in the International Class and E-School programs at the Faculty of Economics and Business, Universitas Pasundan. The International Class and E-School are strategic initiatives designed to strengthen academic service quality, enhance the program’s image, and improve the learning experience of students in a global and technology-based environment. The research employed a quantitative approach with a survey method involving 107 students from the 2016–2023 cohorts who participated in the International Class and/or E-School programs. Data were collected through a structured questionnaire measuring service quality, program image, and student satisfaction using a Likert scale. The instrument was tested for validity and reliability before being administered. Descriptive analysis was used to portray student perceptions, while multiple regression and path analysis were applied to examine the partial and simultaneous effects of service quality and program image on satisfaction. The results show that both service quality and program image are perceived to be in the good to very good category, with overall mean scores above 4.00. Regression analysis indicates that service quality and program image have a positive and significant effect on student satisfaction, with a coefficient of determination (R²) of 0.86, meaning that 86% of the variance in satisfaction is explained by these two variables. The study concludes that improving service reliability, responsiveness, and learning facilities, along with strengthening the program’s academic reputation and international branding, is crucial to sustaining and enhancing student satisfaction.